Parathyroid Adenoma in a Young Female Presenting Multiple Fractures and Postoperative Hungry Bone Syndrome - Hari Hendarto; Laurentius A Pramono; Dante S Harbuwono; Em Yunir; Imam Subekti (Acta Medica Indonesiana)
a young18-year-old female patient with general bone pain and history of multiple fractures brought her to our medical attention. Laboratory work showed hypercalcemia and high parathyroid hormone levels in the blood. Radiograph imaging revealed severe scoliosis with multiple vertebrae fractures with decreased bone mineral density.  Sestamibi showed parathyroid adenoma. This case emphasizes the importance of maintaining a primary hyperparathyroidism as a differential diagnosis when a young patient presents with a multiple pathologic fractures history.